Glucagon-like peptide 1 agonists: a ray of hope for the treatment of polycystic ovarian syndrome - Babar, Areesha; Ali, Rabbiya; Zuhair, Varisha (Journal of the Pakistan Medical Association, 2023)
Dear editor, The Glucagon-like-peptide receptor- 1, agonists belong to a class of drugs that have been used to treat type 2 diabetes. Liraglutide and Semaglutide are drugs of this class, commonly sold under the brand names Saxenda and Wegovy respectively. These drugs have also been approved by the FDA for weight loss in diabetic and non-diabetic obese people.1 The mechanism of action of GLP-1 agonists involve stimulating insulin secretion and delaying gastric emptying. Moreover, GLP-1 receptors are found on adipose tissue, where they promote the conversion of stored fat into energy. They also target the appetite center in the hypothalamus which increases satiety and reduces food intake to cause weight loss. A large number of females who struggle with obesity, concomitantly suffer from Polycystic Ovarian syndrome (PCOS) also which is a multifactorial endocrine disorder in women of reproductive age, affecting 4-20% women around the world.2 One of the major manifestations of this syndrome is weight gain and difficulty in losing it. In contemporary medicine, the treatment of PCOS is limited to lifestyle intervention and symptomatic management. Thus, the patients of PCOS are often told by their doctors to simply lose weight. Physicians around the world agree that weight loss is crucial for women with PCOS who are obese to attain better metabolic, reproductive, and cardiovascular outcomes, because if not treated, obesity worsens the presentation of PCOS. But it is noteworthy that the ongoing hormonal imbalances, increased appetite and insulin resistance in this syndrome, all work against the body’s natural mechanism to lose weight and make it extremely difficult for the patient. This creates a dire need for external interventions regarding weight management in PCOS. Where conventional methods like dietary modifications and exercise alone do not provide substantial results, GLP-1 agonists can be a breakthrough for the management of PCOS since recent research and clinical data also provides evidence of correlation between obesity, GLP-1 kinetic alterations, and pathophysiology of PCOS.3 Hence the use of GLP-1 agonists can be a viable option for treatment of PCOS as multiple clinical trials have shown significant weight reduction, decrease in testosterone levels, improvement in insulin sensitivity and menstrual cycles.4 As the prevalence of PCOS continues to rise in Pakistan, the major presenting complaints include; weight gain, facial hair, acne and menstrual irregularities in teenage girls and infertility in married females. —Continue